The Role of New Media Tools in Marketing for Goods and Services (Raparin Journal of Humanities (RJH), 2021)
This research is an attempt to determine the role of new media tools in marketing for goods and services through a sample of marketing companies for goods and services. This research refers to the way marketing and electronic marketing equipment are used, and the most used marketing tools in the Kurdistan Region are.The most important outcomes researchers have received are the art of marketing in new media forms, due to the nature and technique of new media forms and the number of use by participants. According to the majority of Facebook research samples, it comes in the first rank in the marketing process for services and this seems to be because the number of Facebook users is higher than any other network Facebook's options and usage options are also easier to market and the YouTweed social network has the least use in the marketing process, which may be because of it, which would make it more skilled to prepare a video for the marketing process. In the app chats, Viber comes first to marketing and telegram has the least users, and this is because of the wide and familiarity of people with App Viber, which the research samples believe It is more successful in the marketing process and the app ity of the architecture is because a small number of users are familiar with it, so it is not very successful in the marketing process. Also, about the role of new media forms, the website comes in the first place and the blog comes in the rank of co-coordinator because the blog in the research community is not cared for and people don't have information about it.